"I Post, therefore I Become #cosmopolitan": The materiality of online representations of study abroad in China. Issue 3 (31st January 2020) - Lee, Kris Hyesoo
Abstract: Drawing on social media content created by Western‐situated transnational students as well as two international branch campuses in China, this article scrutinises the textual and visual rhetoric made available by transnational students and international branch campuses for public consumption. Particularly, it describes the ways in which intranational branch campuses and transnational students co‐produce, perform, and curate cosmopolitan sensibilities through social media. Theoretically, this paper proposes the analytical lens of materiality as one way to understand the narrative strategies employed by international branch campuses to construct China as a unique and desirable destination for international education, and by transnational students from North America and European countries to exhibit cosmopolitan practices within domains of their everyday life in China.